LOCATION PECULIARITIES AND EVOLUTION OF KOSHKARCHAY COPPER-PORPHYRE FIELD (LESSER CAUCASUS, AZERBAIJAN) - Mansurov М. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper deals with peculiarities of location and evolution features of Koshkarchay copper-porphyritic field of Murovdagh ore province. Major factors of concentration of copper-porphyritic mineralization in rocks of gabbro-diorite-granodiorite formation has been revealed. It has been established that the structure of this ore region was formed as a result of successive alteration of some deformation stages accompanied by development of fractures in intrusive massive, by dike intrusions, blocks displacements along faults and the fractures composed of various mineral associations. It has been made clear that the copper-porphyritic mineralization is related to the wide halo of hydro-thermal-deformed rocks, frequently observed with clearly outlined ore-metasomatic zones. The general column of metasomatic zonation within the limits of ore region and fields are expressed by successive alteration of the following metasomatic zones: quartz → kalifeldspath → quartz-sericite → argillizated → propylitic. Based on structural-morphological features it can be stated that mineralization in Koshkarchay field is stockwork-vein deposit of embedded type in which the impregnations dominate over veins. The major useful component is copper. Its percentage within stockwork body varies within the broad range – from 0.2 to 2.5 %, with average 0.41 %. Among the mineral resources significantly impacting the importance of the field the molybdenum and precious metals can be indicated. In some intervals the average gold content is 2.0 grams/ton and higher. High silver content was also identified and its value reaches 30-45 grams/ton and this may positively impact the whole value of the field. Results of factor analysis of well data allowed identifying geochemical associations for localization of the areas of mineralization at various stages of evolution of porphyritic-epithermal system. Values of Ф1 factor correlate with quantity of chalcopyrite, bornite and pyrite and from this it can be inferred the tie of geochemical association of Cu (Mo, Pb, Sb) to the early chalcopyrite-bornite-pyrite mineralization of porthyric stage of structure evolution. Values of Ф2 factor referring to the association Mo (Cu, Pb, Co), statistically are related to the content of chalcopyrite and molybdenite, which are the main mineral paragenesis of copper-molybdeneporphyritic mineralization. Thermal-pressure and chemical methods applied for researches on impregnations of ore of pyrite-chalcopyrite, galenitesphalerite-chalcopyrite stages in quartz made it possible to describe the fluid mode of ore formation in this field. Ore-forming hydrothermal solutions by the data of researches on fluid impregnations were the chloride-sodium type, salt concentrations varied from 20 to 30 mass % – eqv. NaCl. Ore components were transferring by these solutions in a form of complex ions containing chlorides of Na and K, rarely sulfates and carbonates. Ore forming process was going under temperatures of 350-2000 С. The certain range of physical and chemical parameters and chemical composition of ore forming fluid corresponds to each type of mineralization. The study results enabled us to define temperatures of homogenization of impregnations and evaluate temperatures of fluids during mineralization at each stage, as well as to define concentrations of major salt components. Complexity of targets evidence high perspectives of copper-porphyritic areas and areas outlined in a range of perspective ore fields.